Synergy of Language and Faith: English Week Immersion Program as a Platform for Religious and Linguistic Development - Novitasari, Dwiana; Susani, Mar'atus; Nur Syah Putri, Selzhafani (Journal of English for Academic and Specific Purposes (JEASP), 2025)
This study explores the integration of language acquisition and religious education through the implementation of English Week at Gontor Modern Islamic Boarding School in Ponorogo. The primary aim is to examine how this initiative fosters both linguistic proficiency in English and a deepened understanding of Islamic values among students. The research employs a case study approach, utilizing qualitative methods including participant observation, interviews with educators and students, and document analysis to collect data. The study highlights how English Week serves as an immersive platform where students not only improve their English skills but also engage in activities that align with the school’s religious teachings. The findings indicate that the English Week program enhances the students' communicative competence in English while reinforcing their religious identity and values. Furthermore, it demonstrates the synergy between language development and faith, suggesting that bilingual education in a religious context can promote holistic student development. The research also reveals the impact of English Week on the students' attitudes toward language learning and religious practices, showing that the program fosters a sense of pride in both their linguistic and religious abilities. The study concludes by offering insights into the potential for integrating English language programs with Islamic studies in other pesantren settings, advocating for a balanced approach to global literacy and religious education. The results emphasize the importance of creating a supportive, immersive learning environment that cultivates both academic and spiritual growth.